Service Quality Pada Koperasi PT. PLN (Persero) Wilayah Sumatera Barat (Factor Analysis) - Dessi Susanti (Universitas Negeri Padang, 2019)
The purpose of this study were 1) to determine the factors that influence service quality on cooperative PT. PLN (Persero) Region West Sumatra, (2) to determine dominant factor influencing service quality on cooperative PT. PLN. This research is an exploratory study. The study population was cooperative members which amounted to 393 people. and technique sampling which numbered 80 people. The data analysis technique used is the analysis of factors. The results showed, namely (1) the assurance factor with a value of eigenvalues of 7324, (2) the reliability factor with a value of eigenvalues of 4855, (3) The responsiveness factor with the value of eigenvalues of 1,727, (4) personal factor with eigenvalues value amounted to 1,294, (5) the empathy factor with eigenvalues value of 1,081, and, 6) the tangibles factor with eigenvalues value of 1,039. In generally the service quality can be categorized as good, because the value of eigenvalues formed above 1. The author suggests to further improve assurance factor for the most dominant factor influencing service quality on cooperative PT. PLN. reliability factor, responsiveness factor, tangibles factor, personal factor and empathy factor also need to be considered, because these factors also affect the service quality on cooperative PT. PLN (Persero) Region West Sumatra.